Risk of Endophthalmitis in Boston Type 1 Keratoprosthesis Combined with Vitrectomy and Silicone Oil Insertion. (25th July 2019) - Abou Shousha, Mohamed; Eleiwa, Taher; Gibbons, Allister; Smith, Christopher; Edelstein, Sean; Kontadakis, George; Schmitz, Zachary; Abernathy, Joshua; Chod, Ross; Bodnar, Zachary; McDaniel, Kelvin; Bentivegna, Rocio; et al.
Abstract : Purpose . To identify the incidence of endophthalmitis and visual outcomes in eyes with Boston type 1 keratoprosthesis combined with pars plana vitrectomy and silicone oil insertion (KPro + PPV + SOI) as compared to eyes receiving Boston type 1 keratoprosthesis (KPro) alone. Patients and Methods . Retrospective chart review of 29 eyes of 27 patients with KPro having at least 12-month follow-up. Thirteen of these eyes had hypotony and/or retinal detachment in addition to corneal pathology and thus received KPro + PPV + SOI. Polymyxin-trimethoprim with a quinolone was used as chronic topical antibiotic prophylaxis in both groups after the first postoperative month. Outcome measures recorded at the 1-, 3-, 6-, 12-, and 24-month follow-up visits included best-corrected visual acuity (BCVA) and rates of postoperative complications. Results . All the patients had completed 24-month follow-up except one case in the KPro group who lost to follow-up after 12-month visit. In the KPro + PPV + SOI group, no eyes had developed endophthalmitis by the 24-month follow-up visit versus 5 eyes of 5 patients in the uncombined KPro group (P = 0.048 ). The 2-year cumulative endophthalmitis incidence was 31.2% in the KPro group versus zero in the KPro + PPV + SOI group (P = 0.030 ). Four of these 5 eyes had vitreous taps with positive cultures; 2 were positive with Staphylococcus aureus, 1 with coagulase-negative staphylococci, and 1 with Streptococcus pneumoniae . Other complications included KPro extrusion (1 in each group), retinal detachment (2 in the KPro and 1 in the KPro + PPV + SOI group), newly developed glaucoma (2 in each group), and retroprosthetic membrane (9 in the KPro and 5 in the KPro + PPV + SOI group). The KPro group had better average preoperative BCVA compared to those of the KPro + PPV + SOI group (−2.29 ± 0.72 LogMAR, versus −2.95 ± 0.30 LogMAR;P = 0.004 ). No statistically significant difference in BCVA was noted in subsequent follow-up visits. Conclusion . The addition of PPV and SOI to the KPro implantation in the eyes with corneal pathology, as well as hypotony and/or retinal detachment, is a safe and effective procedure for visual rehabilitation. Pars plana vitrectomy and silicone oil insertion may have a protective effect against the development of postoperative endophthalmitis in eyes receiving KPro.